Green and Social Regulation of Second Hand Appliance Markets: the Case of Air Conditioners in the Philippines - Babette Never (Circular Economy and Sustainability, 2022)
Second hand markets for appliances such as air conditioners are largely unregulated in many low and middle income countries this far. Energy and climate goals may require a speedy phase-out of old appliances, whereas material resource and social concerns may call for repairing and reusing air conditioners as long as possible. Demand for space cooling is soaring globally, increasing regulatory pressure. In middle income countries such as the Philippines, the market for second hand room air conditioners is sizeable. This study targets the question when and how to regulate the market for used air conditioners to balance green and social goals. It analyses the second hand market for air conditioners in Metro Manila, uncovering the general supply chain, business models and customers as well as energy efficiency, refrigerant and repair practices. The study draws on qualitative interviews with 10 experts and 29 retailers and technicians active in the semi-formal second hand market for air conditioners. Available information of lifecycle analyses is taken into account, but the focus of this contribution lies on social impacts of potential regulation. Overall, short-to-medium interventions in the second hand market are required to balance environmental and social goals that target the different players in the market: construction industry, brokers, retailers and technicians, customers and scrap dealers. Neither a complete ban nor delaying or foregoing regulation is advisable. Specific policy recommendations are derived.
Keywords: 330; Air conditioners; Philippines; Energy efficiency; Climate change; Reuse; Repair